2014
DOI: 10.1016/j.jad.2013.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety disorders in adolescents and psychosocial outcomes at age 30

Abstract: Background Anxiety disorders are associated with adverse psychosocial functioning, and are predictive of a wide range of psychiatric disorders in adulthood. Objective The present study examined the associations between anxiety disorders during childhood and adolescence and psychosocial outcomes at age 30, and sought to address the extent to which psychopathology after age 19 mediated these relations. Method Eight hundred and sixteen participants from a large community sample were interviewed twice during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
188
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(199 citation statements)
references
References 58 publications
5
188
0
6
Order By: Relevance
“…A significant relationship between anxiety and addictive behaviors, and technological addictions in particular, has been repeatedly demonstrated (Andreassen et al 2016;Buckner and Schmidt 2009;Cooper et al 2014;Essau et al 2014;Lee and Stapinski 2012;Parhami et al 2014;Sareen et al 2006;Van Der Maas 2016). Furthermore, anxiety-related factors such as sensitivity to stress, perceived uncontrollability, and avoidance have also been shown to be associated with addiction severity (Forsyth et al 2003).…”
Section: Anxietymentioning
confidence: 97%
“…A significant relationship between anxiety and addictive behaviors, and technological addictions in particular, has been repeatedly demonstrated (Andreassen et al 2016;Buckner and Schmidt 2009;Cooper et al 2014;Essau et al 2014;Lee and Stapinski 2012;Parhami et al 2014;Sareen et al 2006;Van Der Maas 2016). Furthermore, anxiety-related factors such as sensitivity to stress, perceived uncontrollability, and avoidance have also been shown to be associated with addiction severity (Forsyth et al 2003).…”
Section: Anxietymentioning
confidence: 97%
“…Anxiety disorders, estimated to affect 10-20% of adolescents, are the most prevalent mental health disorders in youth and often predate depression (Costello, Egger, & Angold, 2005;Essau, Lewinsohn, Olaya, & Seeley, 2014;Merikangas et al, 2010;Sapru et al, 2016;Wittchen, Kessler, Pfister, Höfler, & Lieb, 2000). These disorders are associated with low self-esteem, poor problem solving skills, social inhibition, and a strong desire to be accepted (Anderson, Williams, McGee, & Silva, 1987;Khalid-Khan, Santibanez, McMicken, & Rynn, 2007;McGee et al, 1990;Twenge, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…8). Of the 5 studies included, 2 reported a signifi cant reduction in self-reported anxiety (p < .05), while 3 studies did not Chu et al, 2016;Essau et al, 2014). Using the random-effects model, the pooled effect size was moderate and the heterogeneity was not signifi cant (g = 0.45; Q (4) = 2.73; I 2 < .001; p = .604].…”
Section: H) Pre-to Post-meta-analytic Depression Outcomes In T-cbt Vsmentioning
confidence: 98%
“…In the prevention area, EMOTION: "Coping Kids" Managing Anxiety and Depression is a transdiagnostic intervention aimed to reduce the likelihood of an anxiety and/or depressive disorder (Kendall, Stark, Martinsen, O'Neil, & Arora, 2013). Finally, Essau and colleagues examined the effectiveness of a transdiagnostic anxiety disorder prevention protocol, Super Skills for Life (Essau & Ollendick, 2013;Essau, Lewinsohn, Olaya, & Seeley, 2014).…”
Section: Introductionmentioning
confidence: 99%